Dynamics of a family of cyan fluorescent proteins probed by incoherent neutron scattering. Issue 152 (6th March 2019) - Golub, Maksym; Guillon, Virginia; Gotthard, Guillaume; Zeller, Dominik; Martinez, Nicolas; Seydel, Tilo; Koza, Michael M.; Lafaye, Céline; Clavel, Damien; von Stetten, David; Royant, Antoine; Peters, Judith
Abstract : Cyan fluorescent proteins (CFPs) are variants of green fluorescent proteins in which the central tyrosine of the chromophore has been replaced by a tryptophan. The increased bulk of the chromophore within a compact protein and the change in the positioning of atoms capable of hydrogen bonding have made it difficult to optimize their fluorescence properties, which took approximately 15 years between the availability of the first useable CFP, enhanced cyan fluorescent protein (ECFP), and that of a variant with almost perfect fluorescence efficiency, mTurquoise2. To understand the molecular bases of the progressive improvement in between these two CFPs, we have studied by incoherent neutron scattering the dynamics of five different variants exhibiting progressively increased fluorescence efficiency along the evolution pathway. Our results correlate well with the analysis of the previously determined X-ray crystallographic structures, which show an increase in flexibility between ECFP and the second variant, Cerulean, which is then hindered in the three later variants, SCFP3A (Super Cyan Fluorescent Protein 3A), mTurquoise and mTurquoise2. This confirms that increasing the rigidity of the direct environment of the fluorescent chromophore is not the sole parameter leading to brighter fluorescent proteins and that increased flexibility in some cases may be helpful.